Adequate antenatal care service utilizations after the onset of COVID-19 pandemic in Ethiopia: a systematic review and meta-analysis - Wondmeneh, Temesgen Gebeyehu; Solomon Tadesse, Zelalem (Frontiers in Public Health, 2024)
The world faces great difficulty in continuing to provide essential maternity health care after the onset of COVID-19 pandemic. Many women have trouble accessing maternity healthcare due to fear of infection. A decline in the utilization of maternity health services is suggested to worsen adequate antenatal care service utilization. Thus, this study aimed to determine the pooled estimate of adequate antenatal care service utilization after the onset of COVID-19 in Ethiopia.The searching of articles was carried out on Web of Science, Scopus, PubMed, CINHAL, Google Scholar, African journals online, and the institutional repository of Ethiopian universities. Using a Microsoft Excel standardized spreadsheet, the data were extracted. A random effect model was used to determine a pooled estimate of adequate antenatal care utilization. I 2 statistics were used to quantify the Conclusion: In this review, the percentage of women who utilized adequate antenatal care after the onset of COVID-19 pandemic in Ethiopia was less than half. Early antenatal care visit is an important factor to achieve adequate antenatal care service utilizations.